Virulence and transmission success of the malarial parasite Plasmodium falciparum - Hayward, Rhian E. (The National Academy of Sciences, 1999)
Virulence of Plasmodium falciparum is associated with the expression of variant surface antigens designated PfEMP1 (P. falciparum erythrocyte membrane protein 1) that are encoded by a family of var genes. Data presented show that the transmission stages of P. falciparum also express PfEMP1 variants. Virulence in this host–parasite system can be considered a variable outcome of optimizing the production of sexual transmission stages from the population of disease-inducing asexual stages. Immunity to PfEMP1 will contribute to the regulation of this trade-off by controlling the parasite population with potential to produce mature transmission stages.